Morphological Characterization of Four Selected Spider Plant (Cleome Gynandra L.) Morphs from Zimbabwe and Kenya - Masuka , A; Goss , M.; Mazarura , U (Asian Journal of Agriculture and Rural Development, 2012)
Faced with climate change one way of adaptation is to reach into the genetic resource of the so-called miner crops. These crops are thought to be more resilient to climate change while being more nutritious than the modern vegetables. It is vital to characterise these crops in order to gather information that will help in their widespread usage. The objective of this study was to morphologically characterise four morphs; three from Zimbabwe and one from Kenya under greenhouse conditions at the Crop Science Department of the University of Zimbabwe, Harare, Zimbabwe. This work assessed number of days to seedling emergence, number of days to flowering, number of leaflets/compound leaf and number of pods/plant and other parameters. The analysis of variance for all the traits exhibited significant differences (P=0.05). There was significant variation among spider plant morphs in plant height, petiole length, length of leaflet, fruit length, fruit width, days to seedling emergence, days to flowering, number of leaflets per compound leaf and number of pods per plant. Morphs from different locations exhibited variability for stem pigmentations. The Kenyan morph differed from the Zimbabwean morphs as it was smaller and produced a higher number of pods per plant. We recommend further studies to reveal the molecular markers associated with the morphological differences we observed.